Self‐Assembled Heterojunction Carbon Nanotubes Synergizing with Photoimmobilized IGF‐1 Inhibit Cellular Senescence. Issue 18 (7th July 2016) - Chen, Wu‐Ya; Yang, Run‐Cai; Wang, Hui‐Min; Zhang, Li; Hu, Kaikai; Li, Chu‐Hua; You, Rong; Yin, Liang; Guan, Yan‐Qing
Abstract : Synthesis of artificial and functional structures for bone tissue engineering has been well recognized but the associated cell senescence issue remains much less concerned so far. In this work, surface‐modified polycaprolactone‐polylactic acid scaffolds using self‐assembled heterojunction carbon nanotubes (sh‐CNTs) combined with insulin‐like growth factor‐1 are synthesized and a series of structural and biological characterizations are carried out, with particular attention to cell senescence mechanism. It is revealed that the modified scaffolds can up‐regulate the expressions of alkaline phosphates and bone morphogenetic proteins while down‐regulate the expressions of senescence‐related proteins in mesenchymal stem cells, demonstrating the highly preferred anti‐senescence functionality of the sh‐CNTs modified scaffolds in bone tissue engineering. Furthermore, it is also found that with sh‐CNTs, scaffolds can accelerate bone healing with extremely low toxicity in vivo. Abstract : With particular attention to cell senescence mechanism, surface‐modified polycaprolactone‐polylactic acid scaffolds using self‐assembled heterojunction carbon nanotubes (sh‐CNTs) and insulin‐like growth factor‐1 are synthesized and structural or biological characterizations are carried out. The highly preferred anti‐senescence functionality of such scaffolds in bone tissue engineering is revealed, and with sh‐CNTs, scaffolds can accelerate bone healing with extremely low toxicity in vivo.